Effect of Voiding Position on Uroflowmetric Parameters in Healthy and Obstructed Male Patients - Yazici, Cenk Murat; Turker, Polat; Dogan, Cagri (Urology Journal, 2014)
Abstract Purpose: Uroflowmetry is frequently used and simple urodynamic test, but it may be affected by various factors. Voiding position is one of the factors that can change the results. We tried to compare the uroflowmetric parameters in sitting and standing positions during urination. Material and Methods: A total of 198 patients were enrolled to the study. All patients underwent an uroflowmetry in standing and sitting position at late afternoon (2-4 PM) of two corresponding days with a gravimetric uroflowmeter (Uroscan, Aymed, Turkey). A transabdominal ultrasonography was used to evaluate post voiding residue (PVR). All uroflowmetric parameters and PVR were compared with paired t test or Wilcoxon signed rank test. Results: The median age of study population was 58.0 (36-69) years. There was no statistically significant difference at voided volume of patients in standing and sitting position as it was 271.5 ± 81.8 mL and 274.8 ± 82.4 mL, respectively (P = .505). Mean maximum flow rate (Qmax) during urination at standing position was 15.3 ± 6.7 mL/s while it was 15.0 ± 7.0 mL/s at sitting position (P = .29). Mean average flow rate in standing position was 8.60 ± 4.0 mL/s and 8.25 ± 3.8 mL/s in sitting position (P = .054). There was a statistically significant difference between the median post-voiding residues in standing and sitting urination which was 29.5 (0-257) mL in standing and 47.5 (2-209) mL in sitting position (P < .0001). Other uroflowmetric parameters (time to maximum flow and voiding time) was not statistically different between groups. Conclusion: There are no clinically important uroflowmetric differences between voiding in sitting and standing positions so voiding position may be left to personal preferences during uroflowmetric evaluation.